“TURN ON THE TEACHER FAN...”: A post-occupation analysis on thermal comfort in a university laboratory (Research, Society and Development, 2021)
Previously, in the workplace, people had to seek mechanisms to adapt to the environment in which they were inserted. Nowadays there is already a concern to make changes at the workplace in order to adapt to their users. Thus, it became necessary to invest in research on thermal comfort. Therefore, this article aims to analyze the thermal comfort in a laboratory in the facilities of a university located in the Central West of Minas Gerais, seeking to identify how the design of a space could influence the thermal sensation. The results showed that changes without a priori analysis in the environment in question, increased by 20% points of thermal unconformity, getting out of the comfort range (-0.82